Simplified All‐Solid‐State WO3 Based Electrochromic Devices on Single Substrate: Toward Large Area, Low Voltage, High Contrast, and Fast Switching Dynamics. Issue 3 (1st January 2020) - Cossari, Pierluigi; Pugliese, Marco; Simari, Cataldo; Mezzi, Alessio; Maiorano, Vincenzo; Nicotera, Isabella; Gigli, Giuseppe
Abstract: Electrochromic devices (ECDs) represent one of the most promising energy saving and solar control technology for the market of energy‐efficient building and optoelectronic devices. A continuous and intense effort is currently devoted to the development of effective solid‐state ECDs and their integration in multifunctional systems, such as photoelectrochromics. Here, the fabrication of simplified all‐solid‐state WO3 based ECDs on single‐substrate is reported, demonstrating how the rational design of highly interconnected WO3 columnar nanostructures with Nafion polymer matrix remarkably decreases the charge transport barrier at the hybrid electrolyte/electrochromic interface (EEI), thus determining an impressive improvement of overall device performances. The soft polymer substrate of the electrolyte plays a key role on the formation of WO3 pillar‐like structures and on the increase of interfacial contact area by affecting the vacuum‐deposition WO3 growth. Apart from providing higher transmittance in bleached state, the resulting device, entirely manufactured at room temperature by bottom‐up process, exhibits lower activation voltages (0.5–3 V) and faster switching kinetics (5–10 s) compared with monolithic ECDs based on both bulk and mesoporous WO3 films. Furthermore, the enhanced EEI enables the scale‐up on large area and flexible substrate ensuring simultaneously a wide optical contrast (Δ T = 70%), and high coloration efficiency. Abstract : The interface engineering of highly efficient all‐solid‐state WO3 based electrochromic device is presented. The formation of a hybrid interface layer based on WO3 pillar‐like structures/polymer Nafion determines a remarkable decrease of charge transfer barrier and increase of interfacial area. Superior device performances than porous and bulk WO3 film‐based device are corroborated by the higher ion mobility and diffusion coefficients.